Corridors for Shared Prosperity - International Finance Corporation (Washington, DC, 2017)
Corridors of Shared Prosperity is the collaborative effort of IFC, a member of the World Bank Group and Intellecap to accelerate the transfer of inclusive business models across developing countries. It consists of knowledge and information around What works in successful transfer. Eleven inclusive businesses, which expanded from India to other developing countries, and over forty four industry practitioners interested in the issue of transfer were consulted to gather empirical evidence. The insights resulting from this analysis have been used to create a framework and roadmap to inform systematic inclusive business transfer with a specific focus on India-Africa transfer. Additional knowledge resources that use the framework as a foundation have also been created. These include a deep-dive report, a companion guide with detailed case studies and a downloadable toolkit comprising of a self-diagnostic tool and checklists. Transfer Journeys of Indian Inclusive Business Models is a compilation of eleven case studies that have been used to bring the framework to life. Each case brings out different nuances of transfer, and illuminates how resource constrained inclusive businesses succeeded in taking their models and their impact to new markets.